Perencanaan Jaringan Heterogen 4G LTE Berdasarkan Coverage Area pada Frekuensi Inter-Band di Kota Palembang - Bengawan Alfaresi; Ardianto, Feby; Kurniawan, M Arif (Jurnal Serambi Engineering, 2025)
The city of Palembang has a territorial character consisting of urban, suburban and rural areas. The population in Palembang City continues to grow and spread to all corners of Palembang City. Therefore, the planning of a 4G LTE network requires a complex plan based on the area characteristics and also paying attention to frequency efficiency. This research aims to design a heterogeneous 4G LTE network in the city of Palembang, focusing on the use of inter-band frequency spectrum to increase the network coverage area. The research methodology includes area mapping and analysis of eNodeB requirements in each sub-district. The propagation model used in 4G LTE network planning is the Cost-Hatta model. In this research, we implemented the use of a frequency of 900 MHz for the macro site, a frequency of 1800 MHz for the micro site, a frequency of 2100 MHz for the nano site and a frequency of 2300 MHz for the pico site. The research results show that at the lowest frequency, i.e. using a frequency of 900 MHz, the number of eNodeBs required is 18 eNodeBs on the uplink side and 60 eNodeBs on the downlink side. At the highest frequency of 2300 MHz, the number of eNodeBs required on the uplink side is 24 eNodeBs and on the downlink side is 329 eNodeBs.